EDUKASI MITIGASI BENCANA LONGSOR DAN BANJIR BERBASIS MASYARAKAT DI KELURAHAN SRENGSEM, BANDAR LAMPUNG - Riki Chandra W, Rahmi Mulyasari, Aminudin Syah, Dyah Indriana K, Ashruri, (Jurnal Pengabdian Kepada Masyarakat Sakai Sambayan, 2024)
Community service activities can reduce disaster risk in Srengsem Village, Indonesia, which is prone to floods and landslides during the rainy season. A survey and analysis of the disaster conditions in Srengsem was conducted to develop structural and non-structural mitigation recommendations, which were then conveyed to affected residents and local regional leaders. Structural mitigation recommendations included, for example, reinforcing buildings and installing drainage systems. Non-structural mitigation focused on increasing community preparedness for disasters through activities such as landslide/flood surveys, outreach, coordination, presentations at community meetings, and distribution of posters and pocket books. These activities helped residents and sub-district officials who previously did not have an understanding of disasters and preparedness to become more knowledgeable and able to carry out mitigation actions independently at the community level.